INTERACTION DESIGN OF COMPUTATIONAL THINKING DIGITAL GAME FOR CHILDREN USING USER-CENTERED DESIGN APPROACH - Rizki Ramadhani, Nira
In the 21st Century, technology has become a part of almost everyone’s lives in the world and will keep on evolving. Therefore, people’s way of thinking must be able to follow the technology evolution. Since 2006, computational thinking has been stated as a fundamental skill for everyone which everyone should have as early as possible. In the digital era that is happening now, the suitable computational thinking learning for children is in the form of digital game as an application on smartphones. This final project aims to produce interaction design and user interface of computational thinking digital game. The methodology used in this final project is user-centered design approach. The output of this final project is a high-fidelity prototype which has achieved the usability and user experience goals that was determined from the user research results. The usability and user experience goals are effective to use, learnability, and enjoyable. Usability testing is conducted to validate the achievement of the goals by using several metrics, such as completion rate, Single Ease Question (SEQ), System Usability Scale (SUS), and Intrinsic Motivation Inventory for interest/enjoyment subscale. Other than that, a brief interview with users is also conducted to obtain feedback from them. The completion rate is 97,4%/100% for usability goal effective to use, the SEQ score is 6,12/7 and the SUS score is 70,5/100 for usability goal learnability, and the IMI interest/enjoyment subscale score is 6,02/7 for user experience goal enjoyable. This application has achieved the usability and user experience goals because all the scores from the measurements using those four metrics are above the average.